2015
DOI: 10.3386/w21182
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Variance Risk

Abstract: At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w21182.ack NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 44 publications
11
29
1
Order By: Relevance
“…Our results of the expectations hypothesis tests are also weaker for short horizons. Thus, these results are ultimately consistent with those of Dew‐Becker et al () and Johnson ().…”
Section: Additional Analysessupporting
confidence: 91%
See 2 more Smart Citations
“…Our results of the expectations hypothesis tests are also weaker for short horizons. Thus, these results are ultimately consistent with those of Dew‐Becker et al () and Johnson ().…”
Section: Additional Analysessupporting
confidence: 91%
“…Second, Johnson () concentrates on short horizons. Dew‐Becker et al () show that the variance term structure is only upward‐sloping at the very short end: There is a large difference between the shortest term implied variance and that with 1–2 months to maturity. Our results of the expectations hypothesis tests are also weaker for short horizons.…”
Section: Additional Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the result of predictive regressions that additively decompose longrun VRP into the sum of one-month VRP and a forward VRP that represents compensation that investors earn for exposure to variance risk beyond the first month. The predictive results connect the findings of Dew-Becker, Giglio, Le, and Rodriguez (2015) and Andries, Eisenbach, Schmalz, and Wang (2015) to the findings of van Binsbergen, Brandt, and Koijen (2012) by showing that kurtosis option-spanning portfolios that are based on the spanning theorems of Bakshi and Madan (2000).discount rates for short-term variance cash flows are tightly linked to those of the equity term structure, which in turn are tied to discount rates of short-term dividend cash flows.…”
Section: Introductionsupporting
confidence: 60%
“…the VIX term structure). The paper's empirical focus on variance is therefore motivated by the factor structure result on higher order moments, as well as recent research on the term structure of variance risk premia: by examining Sharpe ratios of trading strategies that effectively sell variance along its term structure, Dew-Becker, Giglio, Le, and Rodriguez (2015) have found that only news about short-run realized variance is priced. In related work, Andries, Eisenbach, Schmalz, and Wang (2015) use the Heston (1993) model and a short option straddle to estimate the term structure of variance risk premia, an object also studied in Aït-Sahalia, Karaman, and Mancini (2015), who find a significant pricejump component in their own estimated term structure of variance risk premia.…”
Section: Introductionmentioning
confidence: 99%